Comparison of IEEE and IEC standards for calculations of insulation levels and electrical clearances for 230 kV air insulated substation - T. Thanasaksiri (2018)
© 2016 IEEE. This paper compares the calculations of insulation levels and electrical clearances for 230 kV air insulated substation based on IEEE and IEC standards. The IEEE Std. 1427 can be applied for phase to ground and phase to phase insulations and electrical clearances calculations. Besides calculations, the simulation tool, EMTP as presents in IEEE Std. 1313.2 can be helpful for estimation the crest voltages at any location in substation. According to IEEE Std. 1427 which taking into account the basic switching impulse insulation levels (BSL), the iterative method is also required. At this voltage level, the procedure for calculations refer to IEC 60071-2 in range I can be applied. To compile with IEC 60071-2 for calculations the insulation levels and electrical clearances, the iteration process accounting for the standard rated switching impulse withstand voltage or BSL is not required but the test conversion factors have to be considered. The relation between insulation levels and electrical clearances applying IEEE and IEC standards are approximately linear. The insulation levels and electrical clearances when applied both standards are not significantly difference.